Evaluasi Penyajian Laporan Keuangan Daerah Berbasis Akrual Pada Badan Pengelola Keuangan Dan Aset Daerah Kabupaten Lampung Timur - Theo, Ahmad Hadi; Ali, Karnila (Jurnal Manajemen DIVERSIFIKASI, 2022)
This study aimed to determine the accrual accounting presentation of regional financial statements for the East Lampung Regency Financial and Asset Management. Data is obtained from observations, documents and face-to-face interviews of all BPKAD activities or activities, East Lampung Regency. Research data analysis was performed using Miles and Huberman model data analysis, namely data reduction, data visualization and conclusion drawing/verification. The results show that the East Lampung Government has presented 7 (seven) main elements of financial statements, which are reports on budget performance, reports on changes in budget balance, balance sheets. accounting balance sheet, the statement of operations, the statement of cash flows, the statement of changes in equity, and the notes to the financial statements (which are not separate from these financial statements). The implementation of regional financial management in East Lampung Regency Government refers to the government accounting standards (SAP) based on accrual accounting. Keywords: Presentation, Regional Financial Statements, Accruals